Quantifying the impact and recovery of South Africa’s manufacturing sales from the COVID-19 pandemic using a time series intervention analysis - Makoni, Tendai; Chikobvu, Delson (Statistics, Optimization & Information Computing, 2026)
The South African manufacturing sector, a cornerstone of the nation’s economy, was significantly affected by the COVID-19 pandemic. Significant disruptions in production networks and supply chains compelled manufacturing firms to adapt their operations. Although there is increasing interest in exploring the effects of the COVID-19 pandemic, quantitative analyses of its impact and recovery across various economic sectors remain limited. This study aims to quantify the pandemic's impact on South Africa’s manufacturing sector using time series intervention analysis. Intervention analysis plays a crucial role in understanding the effects of significant events on time series data, providing essential insights for policy decisions and strategic actions. An intervention function was incorporated into a SARIMA model. A SARIMA (0, 1, 1)(0, 1, 1)12 plus the COVID-19 pandemic intervention and innovative outlier (IO) fitted well to the monthly South African manufacturing total sales. The results indicated that the SARIMA intervention model effectively captured the seasonal patterns in South African manufacturing sales. The sector witnessed a significant decline of 63.99% in total sales in April 2020, immediately following the implementation of the economic lockdown due to the COVID-19 pandemic. The intervention’s impact was abrupt yet temporary, with the sector bouncing back within approximately fourteen months. This analysis highlights the importance of quantitative models, particularly SARIMA models with intervention functions, in comprehending and forecasting the effects of sudden disruptions on all sectors of the economy, including manufacturing. Policymakers and industry leaders may utilise these advanced approaches to foresee and alleviate the impacts of future economic shocks, facilitating informed decision-making and prompt responses.